Synovial fluid proteins are required for the induction of interleukin-1β production by monosodium urate crystals. (2nd September 2016) - Scanu, A; Oliviero, F; Gruaz, L; Galozzi, P; Luisetto, R; Ramonda, R; Burger, D; Punzi, L
Abstract : Objectives : Monosodium urate (MSU) crystal deposition in gouty joints promotes the release of inflammatory mediators, in particular interleukin (IL)-1β. The induction of IL-1β production by MSU crystals requires a co-stimulus. The objective of this study was to determine which part of the synovial fluid (SF) provides co-stimulation to MSU crystals to induce IL-1β in macrophages. Method : The lipidic fraction (LF) and the protein fraction (PF) were isolated from the SF of patients with arthropathies. The PF was subfractionated according to different molecular weight (MW) ranges. THP-1 cells or human primary monocytes were stimulated with MSU crystals in the presence or absence of SF or SF fractions. IL-1β and IL-8 production and IL-1β mRNA expression were assessed by an enzyme-linked immunosorbent assay (ELISA) and quantitative real-time polymerase chain reaction (qPCR). Results : Exposure of monocytes/macrophages to MSU crystals alone induced the moderate release of IL-8 but not of IL-1β. The production of IL-1β required the presence of both SF from patients with inflammatory arthritis (SFi) and MSU crystals. SF from patients with non-inflammatory arthritis, that is patients with osteoarthritis (OA), did not affect the IL-1β production but slightly enhanced the secretion of IL-8. Both MSU crystals and SFi were required for the induction of the IL-1β transcript, which was not expressed in the presence of either stimulus alone. SFi fractionation demonstrated that the MSU crystal co-stimulus was contained in the PF of SFi with MW > 50 kDa but not in the LF. Conclusions : This study shows that the SF of inflammatory arthritis patients, including gout patients, contains proteins required for the induction of IL-1β by MSU crystals in macrophages whereas lipids are not involved.